Geochronology and petrogenesis of gray gneisses from the Taihua Complex at Xiong'er in the southern segment of the Trans-North China Orogen: Implications for tectonic transformation in the Early Paleoproterozoic - Huang, X.; Wilde, Simon; Yang, Q.; Zhong, J. (Elsevier BV, 2012)
The Taihua Complex in the Xiong'er area along the southern segment of the Trans-North China Orogen (TNCO) consists of gray gneisses with minor amphibolites. Zircon U–Pb dating of the gray gneisses reveals at least two episodes of Early Paleoproterozoic magmatism (2.30–2.32 Ga and 2.07–2.19 Ga), each with distinct geochemical features. The Tieluping TTG gneisses of the early suite have very low HREE (YbN = 0.58 − 4.75) and Y contents (2.05–13.2 ppm) with moderate to high [La/Yb]N (14.3–192.6) and Sr/Y ratios (38.5–220.1), pronounced negative Ta–Nb and Ti anomalies but positive Sr and Pb anomalies. The protoliths of these gneisses were most likely derived from partial melting of thickened lower crust with residual garnet and amphibole, and underwent garnet ± amphibole fractionation, plagioclase accumulation and/or fractionation.The Tieluping TTG gneisses have variable zircon Hf model ages (TDM-HfC = 2.48 − 3.06 Ga) and whole-rock εNd(t) values (− 4.89–4.98), and the youngest whole-rock depleted mantle Nd model age (TDM = 2.32 Ga) is close to the crystallization age of the TTG (2318 ± 8 Ma). The protolith of the gneisses formed from a combination of pre-existing continental crust and juvenile materials, implying an Andean-type continental margin arc environment. It is suggested that crustal thickening was the result of accretionary orogenesis accompanied by basaltic underplating. The Ganshugou potassium-rich gneisses of the later suite have low Na2O and high K2O, and show fractionated LREE and nearly flat HREE patterns, with strong negative Ta-Nb and Ti anomalies.They are characterized by negative εNd(t) values (− 5.01 to − 2.33) and heterogeneous zircon εHf(t) values (− 10.65–2.10) with decoupling of zircon Hf model ages (TDM-HfC = 2.64 − 3.23 Ga) and whole-rock Nd model ages (TDM = 2.55 − 2.81 Ga). The protolith of the Ganshugou gneisses was a potassium-rich igneous rock, which was likely the result of partial melting of pre-existing crustal materials at shallow depth, compatible with a post-collisional setting. There is therefore a tectonic transformation from an accretionary orogenesis to an extensional regime as a consequence of post-collisional uplift in the southern segment of the TNCO in the Early Paleoproterozoic.